PERCEPTION OF PEER TEACHING PERFORMANCE IN MICROTEACHING CLASSES - Eki Saputra; Shinta Yolandari (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
The purpose of this study is to investigate the expectations of students in microteaching classes about peer teaching results. This analysis used descriptive methods. Sixth semester students who were pursuing microteaching subjects at the Muhammadiyah University of Bengkulu's English education program were the focus of the study. In this analysis, the investigator used the questionnaire as a guide. The questionnaire was approved and updated from the Professional Growth and Evaluation Handbook for Teacher (2015). The result showed that students perspective on peer teaching success in microteaching classes was classified as negative. It suggests that students should practice a great deal to improve their better teaching efficiency, and it also indicated that students should be taught how to make a good lesson plan before teaching practice to establish an efficient teaching learning process for lecturers.Â Keywords : Microteaching, Teaching Performance, Students Perceptions.